Reduction of endogenous TGF-β increases proliferation of developing adrenal chromaffin cells in vivo - Combs, Stephanie; Krieglstein, Kerstin; Unsicker, Klaus (Journal of neuroscience research, 2000)
Chromaffin cells and sympathetic neurons are derivatives of the sympathoadrenal cell lineage of the neural crest. Although they are similar with respect to many cell biological aspects, chromaffin cells, in contrast to sympathetic neurons, continue to synthesize DNA and proliferate through their whole life span. Large numbers of neural and hormonal signals have been implicated in the regulation of chromaffin cell proliferation based on in vitro studies. We have previously shown that chromaffin cells synthesize and release transforming growth factor-β (TGF-β) and that exogenously applied TGF-β suppresses chromaffin cell proliferation in vitro. We show now that TGF-β is also a physiologically relevant factor in the control of cell division in developing chromaffin cells. We have neutralized endogenous TGF-β in quail embryos using a monoclonal antibody recognizing all three TGF-β isoforms, TGF-β1, -β2, and -β3. Embryos deprived of TGF-β show a prominent increase in numbers of tyrosine hydroxylase (TH)-immunoreactive adrenal chromaffin cells and TH-positive cells incorporating 5′-bromo-2′deoxyuridine. This is the first documentation of the physiological significance of a factor that has been suggested to play a role in the regulation of chromaffin cell mitosis based on in vitro experiments. J. Neurosci. Res. 59:379-383, 2000 © 2000 Wiley-Liss, Inc.
Gesehen am 13.04.2017